TMOD-10. THE ROLE OF IDH1 R132H MUTATION IN GLIOMA – AN INVESTIGATION BY GENOME-EDITING IN HUMAN INDUCED PLURIPOTENT STEM CELLS. (12th November 2021) - Köpp, Alexander; Gawehn, Luzie; William, Doreen; Preussler, Matthias; Richter, Susan; Heide, Michael; Marrone, Lara; Thieme, Anne; Borgmann, Felix Kleine; Mittelbronn, Michel; Capper, David; Schröck, Evelin; et al.
Abstract: BACKGROUND: Hot-spot mutations in the Isocitrate dehydrogenase 1 (IDH1) cause a new catalytic function resulting in the production of 2-HG, a hallmark in the development of low-grade glioma. The tumorigenic mechanism of this mutation as well as the cell of origin are not known and there is a lack of suitable disease models. Thus, we aim to create a model mimicking glioma development by introducing the IDH1 R132H into human induced pluripotent stem cells (hiPSC) and investigate the influence on stem cell properties and cell differentiation in neuronal progenitor cells. MATERIAL AND METHODS: We use CRISPR/Cas9 based genome editing to induce the IDH1 R132H mutation into healthy-control-derived hiPSCs. Successful introduction of the mutation was confirmed on DNA, RNA and protein level. The hiPSCs are then differentiated into cerebral organoids and characterized using transcriptome sequencing and methylation arrays. RESULTS: We successfully introduced the IDH1 R132H mutation into hiPSCs and confirmed expression of the mutated protein by Western Blot. Metabolite measurement using liquid chromatography tandem mass spectrometry (LC-MS/MS) showed a forty times increased concentration of 2-HG in IDH-mutated compared to the wildtype hiPSCs, proving that the mutated enzyme is functional. To investigate effects of IDH1 R132H on cell differentiation, we generated cerebral organoids from our iPSC-models. The IDH1 R132H mutation did not inhibit cell differentiation or maturation of cerebral organoids but led to a downregulation of splicosome, proteasome and DNA repair enzymes as well as an upregulation of ECM components. CONCLUSION AND OUTLOOK: hiPSCs with R132H mutation pose a promising model for investigations on early glioma development. We are currently step-wise including TP53 and ATRX loss of function mutations in our hiPSC models to recapitulating tumor development in vivo.